School youth entrepreneur program in Kubang Pasu Kedah - Hashim, Norashidah; Salleh, A. Razak; Ali, Hassan; Subramaniam, Chandrakantan; Abdul Rahim, Fauziah; Abdullah, Sahadah; Mohamad, Armanurah (2015)
Studies have shown that countries with many entrepreneurs are more developed.Therefore, exposure to entrepreneurship knowledge should be encouraged from the school at an early stage i.e. primary level.However, the existing entrepreneurial programs have less impact on adolescents. In addition, the problem of unemployment among youth after SPM deepened, especially among high-risk youth, whereas students have the potential to contribute to the local community in particular and the country in general.Thus, the School Youth Entrepreneur Program (PURSe) has been designed to help address the problem.The objective of this program is to create awareness about the importance of entrepreneurship, enculturation of school students with hands-on entrepreneurship and cultivate the aspirations of entrepreneurship as a career choice among students after graduation. In this program students are exposed to the concept of entrepreneurship and entrepreneurial activities by combining theory and practice through training, consultation and close monitoring.The program consists of six phases and adds value to existing entrepreneurship programs in schools through hands-on entrepreneurial activities.It has succeeded in creating entrepreneurial awareness and competence among school youth, start-up micro businesses in and outside the school and managed to build human capital by developing entrepreneurship characteristics and positive attitude of school youth such as leadership, integrity, commitment, desire, realistic, teamwork skills and self-confidence.